An internationalization framework for Brazilian higher education and the role played by languages - Liliane Assis Sade (Domínios de Lingu@gem)
Globalization, technological advances, and new geopolitical organizations have impacted the political, economic, and social world systems, generating new ways of engaging with and “being” in the world. Higher education has responded to those changes by devoting efforts to internationalization, acknowledging its contribution to the quality of education and research. In this direction, this paper aims to provide a brief history of the internationalization of Brazilian Higher education, highlighting the language ideologies and policies that underlie the different historic moments, in order to establish the groundwork to propose a successful internationalization plan which is able to answer the demands of the present challenges faced by the Brazilian higher education institutions. Borrowing De Wit et al.’s (2015) conceptualization of internationalization, this paper reflects on some core elements that relate to who should be involved in the process, why and how it should be conducted and to whom it is aimed. Anchored in data provided by the methodological approach of a SWOT analysis, a five-dimension framework is proposed for the development of an institutional internationalization plan that can incorporate the complex variables that involve the process. The analysis developed demonstrates how language and internationalization are interconnected and how different perspectives of internationalization are associated with specific strategic languages. Furthermore, language is seen as a tool to promote internationalization at home, contributing to the internationalization of the curriculum for all, including students unable to go abroad. In this perspective, internationalization at home is viewed as an inclusive and equitable process. Language is also seen as a two-way channel: it values Brazilian identities and cultures while serving to participate in a globalized world. Finally, it acknowledges the fundamental role of language as a tool to welcome and value different cultures. In doing so, it helps individuals reconstruct their identities in new contexts and build a sense of belonging. This, in turn, enables the promotion of multiculturalism, fosters mutual respect, and facilitates cultural integration rather than cultural assimilation.